Fault-Tolerant and Scalable Key Management for Smart Grid - Wu, Dapeng; Zhou, Chi (IEEE transactions on smart grid, 2011)
In this paper, we study the problem of secure key management for smart grid. Since existing key management schemes are not suitable for deployment in smart grid, in this paper, we propose a novel key management scheme which combines symmetric key technique and elliptic curve public key technique. The symmetric key scheme is based on the Needham-Schroeder authentication protocol. We show that the known threats including the man-in-the-middle attack and the replay attack can be effectively eliminated under the proposed scheme. The advantages of the new key management scheme include strong security, scalability, fault-tolerance, accessibility, and efficiency.